2011
DOI: 10.1007/s11064-011-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Age Associated Neuroinflammation on Long Term Bacosides Treatment

Abstract: Bacopa monnieri (L.) is a revered medicinal plant of traditional Indian system of medicine effective against cognitive impairment in ageing and SDAT. In our previous study, long term administration of bacosides was found to exhibit remarkable anti ageing effect, ameliorate age associated neurochemical and neurobehavioral deficits and prevent hippocampal neuronal degeneration in middle aged and aged rat brain cortex. In continuation to the previous study, the present study aims to investigate the neuroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…[65] Long-term treatment (3 months) of old Wistar rats on bacoside-enriched extract significantly attenuated age-associated neuroinflammation in the rat brain cortex by reversing age-dependent increase in pro inflammatory cytokines, iNOS expression, total nitrite and lipofuscin content. [66] Brahmi treatment also reversed age-associated deficits in antioxidant functions, nerve growth factor and tyrosine hydroxylase expression and age-related increase in lipid peroxidation both peripherally and centrally.…”
Section: Bacopa Monnierimentioning
confidence: 83%
See 1 more Smart Citation
“…[65] Long-term treatment (3 months) of old Wistar rats on bacoside-enriched extract significantly attenuated age-associated neuroinflammation in the rat brain cortex by reversing age-dependent increase in pro inflammatory cytokines, iNOS expression, total nitrite and lipofuscin content. [66] Brahmi treatment also reversed age-associated deficits in antioxidant functions, nerve growth factor and tyrosine hydroxylase expression and age-related increase in lipid peroxidation both peripherally and centrally.…”
Section: Bacopa Monnierimentioning
confidence: 83%
“…[63] Betulinic acid, another active ingredient found in Brahmi, suppressed LPS-induced IL-6 production in PBMCs through NF-kB signalling pathway, suggesting that its age-associated benefits may be from suppression of proinflammatory pathways. [64][65][66] In vitro treatment of PBMCs with triterpenoid and bacoside-enriched methanolic fractions of Bacopa monnieri significantly inhibited LPS-activated TNF-α, IL-6 and nitrite production through modulation of proinflammatory mediators. [65] Long-term treatment (3 months) of old Wistar rats on bacoside-enriched extract significantly attenuated age-associated neuroinflammation in the rat brain cortex by reversing age-dependent increase in pro inflammatory cytokines, iNOS expression, total nitrite and lipofuscin content.…”
Section: Bacopa Monnierimentioning
confidence: 99%
“…Several studies have demonstrated the nootropic effect of Bacopa monnieri is imparted via the action of triterpeniod saponin called bacosides that show acetylcholinesterase inhibition, acetyltransferase activation, b-amyloid reduction, and increased cerebral blood flow. 46 Hippophae rhamnoides on the other hand contains high concentration of flavonoids, fat soluble vitamins, folic acid, various fatty acids, phytosterols, essential amino acids and quercetin as the active phytomolecule. The fruit pulp extract Hippophae rhamnoides have a potent antioxidant property that imparts a neuroprotective role by preventing oxidative damages.…”
Section: Discussionmentioning
confidence: 99%
“…45 Several preclinical analysis and clinical trials have proven the efficacy of these plants in management of cognitive deficits in aged population. 16,43,[46][47][48][49][50] Subsequently, metformin in addition to its antidiabtic properties has been also recently recognized as a potential treatment for neurodegenerative disorders such as AD. Studies have shown that metformin prevents apoptotic cascade in endothelial cell type by inhibiting Permeability Transition Pore (PTP) and blocking the release of cytochrome-c that will lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In one BM sample, Rastogi et al found this bacoside profile-bacopaside I (5.37%), bacoside A3 (5.59%), bacopaside II (6.9%), bacopasaponin C isomer (7.08%), and bacopasaponin C (4.18%). 66 The complete assay of BM is an ongoing effort.…”
Section: Chemical Constituentsmentioning
confidence: 99%